Advances in Sexual and Reproductive Rights of Adolescents in Brazil - Regina, Figueiredo; Fernando, Lefèvre (Journal of Women's Reproductive Health, 2016)
The paper presents the incorporation of sexual and reproductive rights in the legislation of Brazil, considering the influence of the discussions that involved the United Nations conferences of Cairo and Beijing. Are described and analyzed the Federal Constitution and federal laws, as the Criminal Code and the Code of Child and Adolescent, besides other legal norms of Brazilian executive power bodies, like the Ministry of Health and Ministry of Education, particularly in the areas of health and citizenship. This process allowed the introduction of new health and education practices in public institutions, offered to the entire population -primarily benefiting women and teenage girls and, then, integrating people in situation of sexual diversity -although there are still problems, such as the occurrence of pregnancies and abortions in adolescence and the underreporting of sexual and gender violence. It is concluded that Brazil has incorporated into its laws the precepts of the sexual and reproductive rights more easily due to the proper moment, which coincided with the creation of new legal instruments and the organization of the national state. Nevertheless, it is still necessary translating these legal advances into practical advances in the public policies and policies focused on people’s needs.
Keywords: adolescents; legislation; sexual and reproductive rights; sexuality; human rights